Effect of Chewing Gums with Different Contents on Salivary Flow Rate, pH and Ion Exchange - Handan Yıldırım Işık (Selcuk Dental Journal)
Objective: Aim of this study is to examine the effects of chewing gums with different contents on the salivary flow rate, pH and ion exchange in healthy subjects. Material and Method: Twenty healthy individuals with DMFT scores of ≤ 4, who did not use any medication or diagnosed with any systemic disease that could change flow and characteristics of saliva were selected as study sample. The unstimulated saliva of all individuals on day one was collected in sterile test tubes. After 24 hours, saliva stimulated by chewing paraffin was collected from each individual as a control group. Then, five different chewing gums were used for 6 minutes for seven days at 24-hour intervals (Vivident Xylit, Oneo White, Trident Recaldent, Fluogum, CB12 Boost). Saliva samples were collected at 0-1, 1-3 and 3-6 minute intervals in graduated sterile test tubes. The pH of saliva collected at the end of each test period was measured with litmus paper to minimize any time-dependent pH changes. Flow rate was calculated in ml/min. Ion exchanges were evaluated according to the spectrophotometric method. Statistical analysis was performed using IBM SPSS Statistics, Version 23.0 statistical program. Statistically significance level was set as p<0.05. Results: Calcium concentration of the collected saliva was found to be higher in the gum group containing tricalcium phosphate than in the other groups. Calcium carbonate containing gum group showed increased salivary flow rate and lower pH when compared to other groups. Conclusion: Chewing gum containing calcium carbonate and tricalcium phosphate may have beneficial effects on the structure of saliva and beneficial effects in terms of oral and dental health. Keywords: Calcium concentration, Chewing gum, Ion Exchange, pH, Salivary flow rate